HOW TO GET A PhD: A HANDBOOK FOR STUDENTS AND THEIR SUPERVISORS - Taswadi Taswadi (Universitas Trisakti, 2007)
AbstractThl's artl'cle I'S compilatl'on of book w!'l'tten by Estelle M. Phillips concerning guidance for readers interested in continuing to study in doctoral program or S3, moreover this book is simple and can be used for every educational purposes of manktnd hankeringto develop one self.AbstractTulisan mi merupakan saduran dari buku yang ditulis oleh Estelle M. Phillips mengenai panduan bagi pembaca yang berminat melanjutkan studi ke program doktoral atau S3,lebih dari itu buku ini temyata juga dapat dipakai oleh setiap nlsan pendidikan yang berminat mengembangkan diri.